Analisis Tingkat Kesehatan Bank dengan Menggunakan Metode RGEC (Risk Profile, Good Corporate Governance, Earning & Capital) pada PT Bank Sulselbar Tahun 2021-2023 - Wardani, Riska; Nuraisyiah, Nuraisyiah; Oktaviyah, Nurafni (BanKu: Jurnal Perbankan dan Keuangan, 2025)
This study aims to analyze the health level of PT Bank Sulselbar in 2021-2023. This study uses a single variable, namely the bank's health level which is measured using the RGEC method. Data collection techniques are carried out through documentation, by collecting data from the bank's official website and other trusted sources. Data analysis is carried out using a quantitative descriptive approach through the calculation and interpretation of financial ratios according to the standards set by Bank Indonesia. The results of this study indicate that the composite rating obtained by PT Bank Sulselbar in 2021 was 84% with a rating of 2 (healthy), in 2022 it was 80% with a rating of 2 (healthy), and in 2023 it was 80% with a rating of 2 (healthy), reflecting the condition of the bank which is generally healthy so that it is considered capable of facing significant negative impacts from changes in business conditions and other external factors.